Scientific Management for Low Rainfall Areas - Bhan, Suraj (Journal of Soil and Water Conservation, 2022)
Nearly 70 per cent of the cropped area is not irrigated. It is area where there is neither dependable Irrigation nor adequate rainfall that cropping offers both poor returns and great instability. Because of the large areas involved, more emphasis should be placed on improving the production potential of low rainfall areas. The introduction of new technology for low rainfall areas and development strategy for such areas based on the available research information is, therefore, an immediate necessity. The emphasis in this paper is on the climate, varietal improvement, soil and nzoisture conservation, fertilizer application and weed control, intensity of cropping and necessary package of practices for such areas.